On Management Accounting and its Application - Dangol, Jeetendra (PYC Nepal Journal of Management, 2011)
Management Accounting; By Prof. Dr. Madhav Raj Koirala, Achyut Gyawali, Ghanendra Fago, Dhruba Subedi and Hiranya Niraula; Published by: Buddha Academic Publishers and Distributors Pvt. Ltd., Kathmandu; First Edition 2010; ISBN: 978-9937-30-111-4; Pages: 612+20; Price: NRs. 595/-